Photochemical access to noncanonical amino acids and modified peptides - Delgado, José Antonio (2024)
This thesis holds new opportunities on the synthetic state-of-the-art for the photochemical elaboration of noncanonical amino acids and exogenous peptides as judged by (i) the incorporation of a desired structural motif as a side chain via the construction of the non-proteinogenic amino acid building block, and (ii) the precise chemoselective manipulation of an endogenous peptide backbone in solid-phase postsynthetic settings. Chapter 1 describes a photoexcited binary EDA complex that promotes site-selective alkylation of dehydroalanine to access unprecedentedly protected unnatural amino acids under biocompatible reaction conditions. The protocol elapses with marked simplicity obviating the need for an external metal/organic photocatalyst. The optimal reaction condition is shown to be compatible with the implementation of NHPI esters and Katritzky salts as electron acceptor substrates for controlled radical generation. The “off-amino acid scaffold” radical approach implements C(sp3)-hybridized radicals from peptides and advanced synthetic intermediates to construct amino acid-pendant noncanonical motifs. Moreover, no reaction re-optimization was required to successfully prepare another family of enantioenriched amino acids when the Karady-Beckwith alkene was subjected to hydroalkylation. Overall, the protocol was characterized by the wide nature of alkyl radicals employed, mild conditions, and functional group compatibility with chemical yield ranging from moderate to excellent (up to 90% yield). Chapter 2 introduces the concept of merging metallaphotocatalysis with solid-phase peptide synthesis for the diversification of native amino acid side chains under postsynthetic settings. As a result, a highly efficient solid-phase side-selective arylation reaction for editing the N(in)-moiety of tryptophan residues in biologically relevant oligopeptides without damaging native redox-sensitive side chains is described. The transformation proceeds with fully orthogonal chemoselectivity obviating substrate-pre functionalization requirements, thus allowing one-step modification towards noncanonical atoms. The protocol performs extremely well in congested environments such as on-resin fully protected peptides and is suited for chemical biology applications as it accomplishes bioconjugation with fluorogenic and affinity probes, biopolymers, and biologically relevant entities. This solid-phase metallaphotoredox method proves to be robust in arylating an array of challenging biologically active tryptophan-containing peptides (e.g., Valorphin, Spinorphin, Urotensin II, Somatostain, Temporin L, Cholecystokinin, Penetratin, Cosyntropin, Melittin, Glucagon, etc.) no matter where the position or topology in the sequence the tryptophan residue is. The tolerance of the free N-terminal drives stepwise and multifold arylations with subsequent backbone elongation. Thus, this approach streamlines the process of derivatizing bioactive molecules, rendering them more “drug-like”. This expedites the lead optimization process, resulting in the timely development of a clinically viable candidate.